Sixty years of genome biology - Doolittle, W; Fraser, P; Graveley, B; Gerstein, M; Henikoff, S; Huttenhower, C; Oshlack, A; Ponting, C; Rinn, J; Schatz, M; Ule, J; Weigel, D; et al. (BioMed Central, 2013)
Sixty years after Watson and Crick published the double helix model of DNA's structure, thirteen members of Genome Biology's Editorial Board select key advances in the field of genome biology subsequent to that discovery.